Prevalence of Complications Following Unifocalization and Pulmonary Artery Reconstruction Procedures. Issue 6 (November 2020) - Mainwaring, Richard D.; Patrick, William L.; Dixit, Mihir; Rao, Akhil; Palmon, Michal; Margetson, Tristan; Lamberti, John J.; Hanley, Frank L.
Background: Unifocalization and pulmonary artery reconstructions have been developed to treat complex disorders of pulmonary artery development. These procedures require extremely long periods of cardiopulmonary bypass (CPB) to facilitate surgical repair. The objective of this study was to document the prevalence of complications in patients undergoing unifocalization or pulmonary artery reconstructions associated with prolonged periods of CPB. Methods: This was a retrospective review of 100 consecutive patients who underwent unifocalization (n = 66) or pulmonary artery reconstructions (n = 34) with CPB times in excess of five hours. Thirty-eight of these operations were primary procedures, whereas 62 were reoperations. Results: The median age at surgery was 15 months, median duration of CPB was 473 minutes, median number of postoperative complications was 5, and the median length of hospital stay was 24 days. The most frequently encountered complications were low cardiac output (43%), open sternum (40%), reintubation (24%), arrhythmia (17%), and bronchoscopy (17%). There was a correlation between the total number of complications and overall length of hospital stay ( R 2 = 0.64). Major adverse cardiac events (MACE) occurred in 11 patients with one hospital mortality. Patients who experienced MACE had a median length of stay that was 35 days longer (56 vs 21 days) than patients who did not experience MACE. Conclusions: The data demonstrate that complications were relatively frequent in this cohort of patients and had a linear association with hospital length of stay. Major adverse cardiac events were encountered at a modest prevalence but had a profound impact on measures of outcome.